Comparative study of microcelluloses isolated from two different biomasses with commercial cellulose - Owi, Wei Tieng (Animo Repository, 2016)
Microcelluloses (MCs) were chemically isolated from two different biomass sources, empty fruit bunches (EFB) and sugarcane bagasse (SCB). The resulting MCs were compared to the commercially available cellulose (MC-Sigma) that was used as a standard. Structural, crystalline, morphological, and thermal properties of all specimens were characterized and compared by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). FTIR analysis verified that the chemical treatments removed non-cellulosic constituents including hemicelluloses and lignin. XRD patterns revealed the crystallinity increment from 43.1% to 52.1% for MC-EFB and 38.9% to 52.4% for MC-SCB. SEM images demonstrated the fibrillar structure of both MC-EFB and MC-SCB, and their surfaces were smoother compared with MC-Sigma. From the TG curves, MC-EFB provided the highest thermal stability, as it had the highest maximum degradation temperature at 345 °C. DSC results showed only one endothermic peak for all specimens. Taken together, these results reasonably confirmed that the MCs from EFB and SCB are comparable to standard MC-Sigma.